Durability of Mortar and Epoxy Bonded Galvanized Steel Mesh Sheets to Concrete Surfaces - Douier, Kais Aiman (2019)
A Master of Science thesis in Civil Engineering by Kais Aiman Douier entitled, “Durability of Mortar and Epoxy Bonded Galvanized Steel Mesh Sheets to Concrete Surfaces”, submitted in April 2019. Thesis advisor is Dr. Rami Haweeleh and thesis co-advisor is Dr. Jamal Abdalla. Soft and hard copy available.